2011
DOI: 10.1111/j.1365-2362.2011.02469.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers for prediction of spontaneous preterm delivery in preterm labour

Abstract: Combined marker could be used as a simple and sensitive parameter for identifying women at risk of spontaneous preterm delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 32 publications
5
46
2
3
Order By: Relevance
“…However, this finding is difficult to apply in clinical settings because the measurement of IL-6 is time-consuming and requires a special detection kit. Other previous studies suggested the combination of the NLR and cervix length as a more sensitive marker for the prediction of preterm birth [21]. In this study, increased CRP levels and DNI values and decreased lymphocyte counts showed significant associations with HCA.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, this finding is difficult to apply in clinical settings because the measurement of IL-6 is time-consuming and requires a special detection kit. Other previous studies suggested the combination of the NLR and cervix length as a more sensitive marker for the prediction of preterm birth [21]. In this study, increased CRP levels and DNI values and decreased lymphocyte counts showed significant associations with HCA.…”
Section: Discussionsupporting
confidence: 63%
“…The lymphocyte count slightly decreased in the PPROM with HCA group, and this result is similar to that reported previously. The NLR is being increasingly used as a predictive marker for spontaneous preterm birth and intrauterine infection in preterm delivery [21, 31]. The NLR increased in the PPROM with HCA group, but only the lymphocyte count showed a relatively high difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…c-reactive protein, neutrophil count, inflammatory cytokines) or genotype, which have been previously correlated in some groups of women with SPTB. 1619 …”
Section: Commentmentioning
confidence: 99%
“…These markers also increase in different obstetric conditions such as spontaneous preterm delivery or gestational diabetes mellitus (17,24,29,30). Studies investigating the relationship between inflammation and HG are primarily focused on the inflammatory markers in the first trimester because HG predominantly occurs in this period.…”
Section: Discussionmentioning
confidence: 99%